Study of a full scale oxy-fuel cement rotary kiln. (April 2019) - Ditaranto, Mario; Bakken, Jørn
Highlights: A full-scale oxy-fuel cement rotary kiln of 3, 000 ton/year clinker capacity has been numerically investigated. The CFD study was part of an iterative optimization procedure with the process modelling of the whole cement plant with full oxy-fuel capture. The optimal rotary kiln operating conditions has an oxygen concentration of 52.1% in the primary oxidizer stream. Abstract: Oxy-fuel combustion has been shown to be an attractive technology to be implemented in cement production with CO2 capture from a process point of view. Due to the market situations and future perspectives it is necessary that the technology can be retrofitted into existing plants. As part of the H2020 EU project CEMCAP, the study presented here investigates the retrofitting of oxy-fuel combustion technology on a typical full-scale cement rotary kiln of 3000 ton/year clinker capacity. The flame generated by a commercial burner has been modelled by CFD with a seven steps combustion reaction model, the k-omega SST turbulence model, and the discrete ordinates radiation model with the Weighted Sum Grey Gas model. The burner is composed of an annular outlet where coal is fed and nozzles from which angled high velocity jets generate a swirling motion for flame stabilization and mixing purposes. As in all rotary cement kilns, a high temperature low velocity secondary oxidizer stream coming from the clinker cooler flows coaxially to the burner in the kiln for heat efficiency purposes. A flame developing in air has been used as a reference case and several oxy-fuel flames have been characterized and compared. The oxy-fuel inlet parameters that are varied in the study are the oxidizer composition and flow rates in both the primary and secondary streams. The work presented is part of an optimization procedure based on iterative interaction with the process modelling of the whole cement plant with full oxy-fuel capture (not presented in this article). With retrofit application in mind, the objective was to reproduce a heat radiation profile to the clinker equivalent to that obtained in the air reference case. The optimized oxy-fuel case is characterized by a primary burner oxidizer of lower flow rate, but with higher oxygen concentration of up to 52.1% to generate the necessary heat in the near burner region.